Amphibians and reptiles recorded from the Lambir Hill's National Park, Sarawak, East Malaysia - Das, Indraneil; Charles, Joseph K. (Centre for Herpetology, Madras Crocodile Bank Trust, 1993)
Ecological data are presented on 20 species of amphibians and reptiles collected and/or observed in the Lambir Hills National Park, Fourth Division, Sarawak, East Malaysia, during two trips made in September, 1992 and August, 1993. Some of the observations were made with the use of a tree-tower on a Dryobalanops lanceolata tree that allowed access 50 m above the forest floor and a tree-walk 15.65 m above ground. Seven species of amphibians and reptiles that are normally associated with human-created environments were also taken, and the total numbers of amphibians and reptiles thus recorded from the Park are 16 and 23, respectively.